Understanding the role of galectin inhibitors as potential candidates for SARS-CoV-2 spike protein: in silico studies. Issue 50 (13th August 2020) - Sethi, Aaftaab; Sanam, Swetha; Munagalasetty, Sharon; Jayanthi, Sivaraman; Alvala, Mallika
Abstract : Galectin 3 have the potential to inhibit the SARS-CoV-2 spike protein. We validated the studies by docking, MD and MM/GBSA calculations. Abstract : The Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2) has been rapidly transmitting and leaving its footprints across the globe. Stringent measures like complete lockdown and extensive testing have been employed by many countries to slow it down in its tracks until a viable treatment is found. Therefore, in the current scenario, prompt solutions need to be uncovered to tackle the virus. In the present study, 330 galectin inhibitors were tested against SARS-CoV-2 spike (S) protein with the aid of molecular docking and molecular dynamics. Finally, the binding free energy and contributing energies were calculated for 2 top scoring ligands by using MM–GBSA method. Many of the galectin inhibitors displayed high binding score against the S protein. They were found to bind to the site of contact of S protein to ACE2. Thus, they show promise of disrupting the ACE2–S protein binding and prevent the virus from invading the host cell. Among the ligands screened, TD-139, a molecule currently in Phase IIb clinical trials, was found to be a potential hit. The present study paves the way for in vitro and in vivo testing of galectin inhibitors against SARS-CoV-2. In addition, it warrants a swift examination of TD-139 for treating COVID-19.